Peningkatan Informasi Potensi Ekonomi Serta Profil PMA dan PMDN Kota Cimahi - Koesworodjati, Yudhi (Jurnal Trikonomika, 2009)
One of the most strategic economy policy to stimulate regional economic growth is increasing the investments. To achieve this, efforts to influence the investor must be taken. This study aim to organizing & mapping potential potential economy of Kota Cimahi; in order to get the new & accurate data information to influence the investor to invest in Kota Cimahi. This study used descriptive method based on problem solving according to field observation. This study show that investment policy must become more focused on two important aspects: internal and external aspect. The internal aspect are building conducive & efficient climate for investment. The external aspect are providing accurate & informative data about regional potential economic of Kota Cimahi.